Erratum - Editorial (Nuclear Technology and Radiation Protection, 2018)
In the article: A new approach on modelling of the B-VIII, the ultimate achivement of the second “Uranverain” by Milan P. PEŠIĆ, published in the Nuclear Technology & Radiation Protection journal, 33 (2018), 1, pp. 1-23, during the technical preparation of the article, the name of German Evonik Industries AG is wrongly spelled as Evronik Industries AG. This misspelling is entirely author''s omission and he sincerely apologies to the Evonik Industries AG and the readers of the Nuclear Technology and Radiation Protection journal. Link to the corrected article 10.2298/NTRP1801001P